PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN HASIL BELAJAR MATA KULIAH KETERAMPILAN BERBICARA - Nur Alfin Hidayati (Universitas Muria Kudus, 2021)
This research is motivated by the low learning outcomes of speaking skills courses for level I students of the PBSI IKIP PGRI Bojonegoro Study Program for the 2020/2021 Academic Year. The purpose of this study was to improve the learning outcomes of speaking skills using the PBL model for level I students of the PBSI IKIP PGRI Bojonegoro Study Program for the Academic Year 2020/2021. This study uses a qualitative description method in the form of classroom action research through two cycles. Each cycle consists of planning, implementing, observing and reflecting. The subject of this research is the level I students of the PBSI Study Program with a total of 30 students. The object of this research is the process of learning speaking skills for the first-level students of the PBSI IKIP PGRI Bojonegoro Study Program in class. Data collection techniques using, observation, interviews, tests, and documents. The data analysis technique of this research uses interactive analysis techniques which consist of three components, namely data grouping, data presentation, and drawing conclusions. The results showed an increase from the pre-cycle of 43.3% which was completed to 73.3% in cycle 1 and in cycle 2 it increased by 100% the level of completeness of student learning outcomes in the speaking skills course. The conclusion of this study is that the application of the PBL learning model can improve the learning outcomes of speaking skills courses for level I students of the PBSI IKIP PGRI Bojonegoro Study Program for the 2020/2021 Academic Year.